Impact of Various Environmental and Growth Conditions on Antigen 43 Gene Expression and Biofilm Formation by Uropathogenic Echserchia coli - Mohammad Arjmand; Ezatallah Ghaemi; Ailar Jamalli (Medical Laboratory Journal, 2017)
ABSTRACT Background and Objectives: Biofilm is a population of bacteria growing on a surface and enclosed in an exopolysaccharides matrix, which increases resistance to antimicrobial agents and immune response. Uropathogenic Escherichia coli (UPEC) are biofilm-forming bacteria and the most common cause of urinary tract infections (UTIs). This study evaluated the effect of different concentrations of glucose, NaCl, blood, serum and urine on biofilm formation and antigen 43 (Ag43) gene expression, as a main gene involved in biofilm formation. Methods: Among E. coli isolates from patients with UTI, four extended-spectrum beta-lactamase (ESBL) and non-ESBL strains, and a standard UPEC strain were selected. Biofilm formation of the strains in brain heart infusion (BHI) broth with different concentrations of glucose, NaCl, sheep blood, serum and human urine was evaluated using microplate method and crystal violet staining. Ag43 gene expression was investigated using Real-Time polymerase chain reaction, SYBR Green dye, and specific primers. Results: Presence of glucose at all concentrations reduced biofilm formation. Presence of 1% NaCl, 1% sheep blood, 10% bovine serum, and 5% urine significantly increased biofilm formation. Expression of Ag43 by the strains grown under 1% glucose, 1% NaCl, 1% sheep blood, 10% bovine serum and 5% urine decreased. Conclusion: All environmental factors other than glucose may increase biofilm formation of E. coli at different concentrations. This is not affected by factors such as isolation from inpatient or outpatients and type of strains (ESBL or non-ESBL). Contrary to our expectations, Ag43 expression is independent of environmental factors and decreases even under the most suitable concentrations. Keywords: Biofilms, Uropathogenic Escherichia coli, UTI, Antigen 43, Real-Time PCR.